Happiness Is Not Always Fun: An Unsuspicious Reading of Ali: Fear Eats the Soul - Hodgson, Naomi (Philosophical Inquiry in Education, 2023)
The film-philosophy of Stanley Cavell has had a clear and ongoing influence on the recent focus on film in educational philosophy. Here, Cavell’s film-philosophy is brought into conversation with the work of the anthropologist Veena Das and the literary theorist Toril Moi to further articulate the educational force of film. The practice of responding to film in terms of its specificity as film and its educational potential is discussed in relation to R. W. Fassbinder’s film Ali: Fear Eats the Soul. Cavell, Das, and Moi are drawn upon to articulate, in a post-critical vein, the invitation to self-examination brought about by the film’s presentation of the ordinary and the violence of the everyday. This reading contrasts, though perhaps sometimes complements, the “hermeneutics of suspicion” seen to characterize critical textual analysis, and recasts, uncomfortably sometimes, the political, from something to be uncovered to something of which we are constitutive.